Application of the Method of Interacting Configurations in the Complex Number Representation to Calculating the Spectroscopic Characteristics of the Autoionizing States of Ве, Мg, and Ca Atoms - Simulik, V. M.; Zajac, T. M.; Tymchyk, R. V. (Ukrainian Journal of Physics, 2019)
The method of interacting configurations in the complex number representation, which was earlier applied to describe helium quasistationary states, has been used for the calculation of ionization processes in more complicated atomic systems. The spectroscopic characteristics of the lowest quasistationary states of the Ве, Мg, and Са atoms in the problem of the electron impact ionization of these atoms are investigated. The energies and the widths of the lowest 1S, 1P, 1D, and 1F autoionizing states of Be and Mg atoms, and the lowest 1P autoionizing state of a Ca one are calculated.